John Alden Carpenter collection - Carpenter, John Alden, 1876-1951.; Carpenter, John Alden, 1876-1951. (1891)
The papers of the John Alden Carpenter Collection, which span the years 1891 to 1961, consist of music, correspondence, writings, photographs, scrapbooks, and other printed materials. The bulk of the collection is the music materials, primarily holograph manuscripts of Carpenter's songs, orchestral pieces, and dramatic works. The holograph manuscripts of the songs include not only his better-known works but also many that have never been published. Carpenter's chamber and orchestral works are well represented also. For many works that Carpenter later arranged or revised, the collection contains both the original and at least one revision. A number of the printed scores of Carpenter's music in the collection feature holograph annotations or alterations. The bulk of the correspondence in the collection consists of letters from Carpenter to Ellen Borden (Mrs. John Borden, also addressed as Mrs. Waller Borden), who became Carpenter's second wife in 1933. This correspondence dates from approximately 1910 to 1935, and although the letters are largely personal in nature, they do contain mention of various specific compositions and productions. The remaining correspondence is that written to Carpenter by various colleagues and friends, including George Whitefield Chadwick, Percy Grainger, Frederick Stock, Leopold Stokowski, and Walter Damrosch. There is also considerable correspondence from the 1940's between Carpenter and his publisher, G. Schirmer. Carpenter's writings in the collection consist primarily of his program notes for works such as Adventures in a perambulator, Skyscrapers, The eeven ages, and the song cycle Gitanjali, as well as the stage works Krazy Kat and The birthday of the infanta. Many of the typescript texts for songs and dramatic works include emendations in Carpenter's hand as well. Numerous photographs and watercolors of the sets and costumes of Carpenter's stage productions are included. The remainder of the collection consists of a variety of biographical materials, programs, and clippings. Three large scrapbooks include not only clippings and programs but also photographs from the stage productions and letters received by Carpenter.
John Alden Carpenter was born in 1876 in Park Ridge, Ill. His earliest musical studies were with Amy Fay and W.C.E. Seeboeck in Chicago and J.K. Paine at Harvard University, from which he was graduated in 1897. Other musical studies included a few lessons with Edward Elgar in Rome in 1906 and four years of study with Bernhard Ziehn in Chicago (1908-12), with subsequent studies under Ziehn disciple Julius Gold in the years that followed. Like his father, Carpenter was by profession in the shipping business, serving as vice-president of the family firm George B. Carpenter & Co. until he retired in 1936 to devote himself entirely to music. Carpenter's musical compositions include both songs and orchestral and stage works. His earliest orchestral work, Adventures in a perambulator (1914) was the first of many successes. The ballet Skyscrapers (1923-24), performed at the Metropolitan Opera House in 1926, was one of the first attempts at a literal depiction of modern American urban life. Other stage works include a "jazz pantomime" entitled Krazy Kat (1921), based on the comic strip by George Herriman, and a ballet-pantomime with Spanish overtones, The birthday of the infanta (1917). Carpenter was also considered an outstanding composer of songs; of particular note are the song cycles Gitanjali (1913, orchestrated 1934), a setting of a collection of poems by Rabindranath Tagore, and Water-colors (1916, orchestrated 1918), based on the writings of Confucius and other Chinese poets. Carpenter's commissions include Song of faith (1932) for the George Washington Bicentennial in 1932, and the Elizabeth Sprague Coolidge commissions of his String quartet (1927) and Piano quintet (1934). Carpenter was a highly successful composer in his day, being named a Knight of the French Legion of Honor (1921) and receiving such honors as the Gold Medal of the National Institute of Arts and Letters. He also received honorary degrees from Harvard University, Northwestern University, the University of Wisconsin, and the American Conservatory of Music.
Additional correspondence of John Alden Carpenter are in a number of other special collections in the Music Division, including the Julius Gold, Percy Grainger, Damrosch-Blaine, Serge Koussevitzky, and Elizabeth Sprague Coolidge collections.
Finding aid available in the Library of Congress Performing Arts Reading Room and on the Internet.
John Alden Carpenter Collection, Music Division, Library of Congress.
Keywords: Carpenter, John Alden, -- 1876-1951.; Carpenter, John Alden, -- 1876-1951 -- Correspondence; Chadwick, G. W. -- 1854-1931 -- Correspondence; Grainger, Percy, -- 1882-1961 -- Correspondence; Stock, Frederick, -- 1872-1942 -- Correspondence; Stokowski, Leopold, -- 1882-1977 -- Correspondence; Damrosch, Walter, -- 1862-1950 -- Correspondence; G. Schirmer, Inc. -- Correspondence